Synthesis of the Dimensions and Components of Information Anxiety - Ali Imanzadeh; Maryam Marandi Heidarluo (نشریه مطالعات دانش‌پژوهی)
Purpose: Information anxiety, a concept that has emerged alongside the expansion of modern epistemologies and the growth of virtual spaces, is increasingly recognized as a significant psychological issue. This research aims to synthesize the dimensions and components of information anxiety, providing a comprehensive understanding of its scope.Methodology: This study employed a qualitative synthesis approach. The research population consisted of studies published between 2014 and 2024. Initially, 139 relevant articles were identified, including 4 in Persian and 135 in English. Following the application of exclusion criteria, 20 studies (16 in English and 4 in Persian) were selected for final analysis. Data were analyzed using Roberts' six-step synthesis model, which involved a three-stage coding process (open, central, and selective).Findings: The synthesis process revealed 143 open codes, 25 central codes, and 5 selective codes, which were categorized into five dimensions of information anxiety: (1) information overload, (2) inability to access information, (3) inability to understand and process information, (4) psychological factors, and (5) inability to manage knowledge.Conclusion: Despite differing perspectives on whether information anxiety is inherently positive or negative, it is clear that this emerging form of anxiety can lead to significant psychological and epistemological consequences. Information anxiety can affect both mental and physical health, thereby influencing individuals' quality of life. Understanding its dimensions and components can empower individuals to manage and mitigate this anxiety effectively.Value: This research is the first synthesis of the dimensions and components of information anxiety. Its findings contribute to the accurate identification of the boundaries and gaps in the current understanding of information anxiety, offering valuable insights for future research and practical applications.